Designing the content of the educational institution information and consulting environment (Educational Dimension, 2020)
In article the definition of the educational institution information and consulting environment has been formulated. Based on the semantic analysis of the constituting categories, it was found the such environment is a relevant part of the information education society, within which it becomes possible to exchange information and consultative support of subjects of the educational process and other stakeholders by means of computer focused technologies. Such an environment is educational, informational, communicatively focused, professionally oriented, developmental, reflexive-contextual, and reflexive-active environment of innovative promotion. The semantic and functional content of the educational institution information and consulting environment have been specified. The components of the information and consulting environment, inextricably linked with the person as a subject of an educational process, have been analyzed. To list of them has been included following: social component that provides satisfaction and development the needs of subjects of educational process advisory assistance of the learning and teaching; spatial-objective one which determines the environmental design; psychological and pedagogical one covering pedagogical and methodological support for the implementation of the goals of the environment. These include: computer-based pedagogical technologies and technologies that provide the appropriate level of advisory services. The pattern of the educational institution information and consulting environment covering organizational, technical methodical resource areas have been established. The benefits and risks of the educational institution information and consulting environment have been reviewed and analyzed. It is substantiated that if a such environment is correctly organized it be possible the implementation of information, consulting, diagnostic, interactive, coordinating, professional and developmental functions and the function of pedagogical and educational support. It is concluded that the organization of information and consulting environment of the educational institution will help increase the efficiency of the educational process and the quality of educational services.